Role of intrinsic disorder in human exonuclease1 regulation - Umar, Aminu Argungu (2017)
Human exonuclease1 (hExo1) is a member of the eukaryotic nuclease family that includes Rad2/Xeroderma pigmentosum complementation group G (XPG), flap endonuclease1 (FEN1) and gap endonuclease1 (GEN1). Human exonuclease1 is involved in multiple DNA metabolism processes, including DNA repair and replication. Most of the fundamental roles of Exo1 have been described in yeast. In this study, hExo1 protein was over expressed from both insect cells and bacteria and over expressed protein was purified to near homogeneity. In this research project, a biochemical characterization of full-length hExo1 is reported. As well as assaying hExo1 on different dsDNA substrates, the factors essential for the thermodynamic stability of hExo1 were determined. It is shown in this study that resection activity and stability of hExo1 on dsDNA is modulated by temperature, pH and salt concentration. The DNA end resection process is a guiding principle to cellular response during DNA double strand break lesion and is pivotal for genome maintenance. Even though insufficient DNA resection restrains homology-directed repair mechanisms and the activation of ATR (ataxia telangiectasia and Rad3 related)-dependent checkpoint, over-resection results in production of an excessive single-stranded DNA that could lead to genomic instability. Nonetheless, the control mechanisms for DNA end resection are not yet understood fully. In this study it is shown that the major resection nuclease hExo1 is both positively and negatively controlled by protein-protein interactions to enable a proper DNA end resection mechanism. This report show that 14-3-3ζ 14-3-3ε proteins interact with the C-terminus region of hExo1 and allosterically control hExo1 DNA end-resection activity while PCNA sliding clamp increases the DNA end resection activity by hExo1. Circular dichroism shows that the C-terminus region of hExo1 is intrinsically disordered with significant polyproline type II conformations. Dynamic Light Scattering and Sedimentation Velocity Analytical Ultracentrifugation results show that a monomeric, partly intrinsically disordered, form persists for hExo1 in solution with an expanded hydrodynamic radius of 118 Å. Taking into consideration the structural propensity of hExo1 and the fact that, more often the binding sites for the 14-3-3 proteins are found within the unstructured regions, this study propose that the disorder-to-order transition of the ligand molecule’s structure might be a model of how hExo1 is negatively control by the 14-3-3 proteins. Results of this project work provide crucial insights into a pioneering process of DNA end resection regulation a critical event in genome maintenance and may be implicative in cancer treatment.